2007
DOI: 10.1529/biophysj.106.091538
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cardiac L-Type Ca2+ Current in Na+-Ca2+ Exchanger Knockout Mice: Functional Coupling of the Ca2+ Channel and the Na+-Ca2+ Exchanger

Abstract: L-type Ca2+ current (I(Ca)) is reduced in myocytes from cardiac-specific Na+-Ca2+ exchanger (NCX) knockout (KO) mice. This is an important adaptation to prevent Ca2+ overload in the absence of NCX. However, Ca2+ channel expression is unchanged, suggesting that regulatory processes reduce I(Ca). We tested the hypothesis that an elevation in local Ca2+ reduces I(Ca) in KO myocytes. In patch-clamped myocytes from NCX KO mice, peak I(Ca) was reduced by 50%, and inactivation kinetics were accelerated as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 22 publications
5
66
0
Order By: Relevance
“…These findings are in line with previous studies in other murine models with altered NCX expression. 16,17 These observations support the hypothesis that reduced Ca 2+ extrusion capacity by reduced NCX activity promotes Ca 2+ -dependent I Ca inactivation by accumulation of Ca 2+ in the dyadic cleft. Thus, next to the genetic suppression of NCX inward current, this direct functional interplay between NCX and I Ca will also contribute to the observed reduction of AP duration and the suppression of EAD in hetKO.…”
Section: Suppression Of Eads: Reduced Ap Duration and Interaction Of supporting
confidence: 75%
See 4 more Smart Citations
“…These findings are in line with previous studies in other murine models with altered NCX expression. 16,17 These observations support the hypothesis that reduced Ca 2+ extrusion capacity by reduced NCX activity promotes Ca 2+ -dependent I Ca inactivation by accumulation of Ca 2+ in the dyadic cleft. Thus, next to the genetic suppression of NCX inward current, this direct functional interplay between NCX and I Ca will also contribute to the observed reduction of AP duration and the suppression of EAD in hetKO.…”
Section: Suppression Of Eads: Reduced Ap Duration and Interaction Of supporting
confidence: 75%
“…Indeed, this has been observed in homozygous knockout mice 16,25 and-conversely-a slowed inactivation was observed in homozygous overexpressor mice. 5,17 In our study, we also observed a trend toward accelerated I Ca inactivation in heterozygous KO mice, however, other than in homozygous KO mice, this trend did not reach statistical significance.…”
Section: Suppression Of Eads: Reduced Ap Duration and Interaction Of mentioning
confidence: 85%
See 3 more Smart Citations